2016
DOI: 10.1111/ajt.13606
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation With Final Allocation Based on the Virtual Crossmatch

Abstract: Solid phase immunoassays (SPI) are now routinely used to detect HLA antibodies. However, the flow cytometric crossmatch (FCXM) remains the established method for assessing final donor-recipient compatibility. Since 2005 we have followed a protocol whereby the final allocation decision for renal transplantation is based on SPI (not the FCXM). Here we report long-term graft outcomes for 508 consecutive kidney transplants using this protocol. All recipients were negative for donor-specific antibody by SPI. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 27 publications
(45 reference statements)
1
27
0
3
Order By: Relevance
“…Because of these issues, the VXM is gaining in popularity as an effective approach for many candidates. The VXM can reduce the time to transplantation and decrease cold ischemia time without impacting allograft survival, patient survival, or early rejection rates . Judicious application of the VXM can then allow for grafts to be shared over extended distances without incident even in highly sensitized recipients .…”
Section: Future Of Crossmatchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these issues, the VXM is gaining in popularity as an effective approach for many candidates. The VXM can reduce the time to transplantation and decrease cold ischemia time without impacting allograft survival, patient survival, or early rejection rates . Judicious application of the VXM can then allow for grafts to be shared over extended distances without incident even in highly sensitized recipients .…”
Section: Future Of Crossmatchingmentioning
confidence: 99%
“…The VXM can reduce the time to transplantation and decrease cold ischemia time without impacting allograft survival, patient survival, or early rejection rates. 40,41 Judicious application of the VXM can then allow for grafts to be shared over extended distances without incident even in highly sensitized recipients. 42,43 Furthermore, eliminating a prospective physical crossmatch has been shown to decrease both time on waiting list and wait list mortality for lung and cardiac transplant recipients.…”
Section: Future Of Crossmatchingmentioning
confidence: 99%
“…This approach has been used successfully in renal transplantation. Johnson et al (80) have reported on a large cohort of patients where the final decision to transplant was based on SAB results rather the FCXM result. When analyzed for clinical outcome based on whether the FCXM was positive or negative, despite the fact the FCXM positive group were more “at risk” than the FCXM negative group, the transplant outcomes were comparable, justifying the use of the VXM in preference to the results obtained by FCXM.…”
Section: The Virtual Crossmatchmentioning
confidence: 99%
“…This method allows for the sensitivity of flow crossmatch combined with identifying specific antibody. Johnson et al found that the final transplant decision could be taken on the basis of the virtual crossmatch irrespective of the flow cytometry without significant difference in the clinical outcome in those who were flow cytometry positive but virtual crossmatch negative [17]. A recent study on pancreas transplants showed a reduced cold ischemia time when virtual crossmatch was used in lieu of flow cytometry [18].…”
Section: The Virtual Crossmatchmentioning
confidence: 99%